Prevalence of Appendix Perforation in Patients Presenting with Acute Appendicitis: A Cross-Sectional Study - Nighat Ghias, Aisha Tasneem, Lekhraj Mal, Abdul Salam Memon, Muhammad Abid Owais, Bushrsa Tasneem, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the frequency of perforated appendix among patients presenting with acute appendicitis. Study design: A cross-sectional study Place and Duration: This study was conducted at Sindh Employee Social Security Hospital Landhi Karachi, Pakistan from July 2020 to November 2021. Methodology: This study includes 205 patients. All the details like age, gender, and previous history associated with diabetes and fasting blood sugar were noted. The surgeries were performed by a single surgeon who detected the presence and absence of a perforated appendix. Results: Mean age of patients was 28 years with a standard deviation of ±13.63. A total of 64% of patients were male and 26% were female. About 11% of patients had perforated appendix after acute appendicitis. Conclusion: The frequency of perforated appendix in this study was 11% in patients undergoing appendectomy for acute appendicitis.